Global Science Literacy
XIV, 242 p.
Keywords: The authors propose the science curriculum concept of Global Science Literacy justifying its use internationally with reference to the nature of science, the probable direction of science in the new millennium, the capability for GSL to develop inter-cultural understanding, and its relevance to non-Western cultures and traditions. GSL curricula are organized conceptually rather than by science discipline, include objectives from the social studies construct of global education, and represent the broad spectrum of science methodologies, not just those of the physical sciences typical of current curricula. The book is recommended reading for all who are interested in the future of science curricula and interested in considering a non-traditional viewpoint. Curriculum developers and researchers, future teachers and graduate students in general curriculum courses, science education courses and social studies education courses, and their professors should be particularly interested. The book is divided into three sections. In the first section, the concept of Global Science Literacy and the justification of its use for science curricula internationally are developed. The second section describes learning environments that are especially appropriate for GSL curricula. The third and last section provides ideas and approaches for developing aspects of GSL curricula.